Chinese Herbal Medicine Therapy Reduces the Risks of Overall and Anemia-Related Mortalities in Patients With Aplastic Anemia: A Nationwide Retrospective Study in Taiwan - Chiu, Mu-Lin; Hsu, Yu-Lung; Chen, Chao-Jung; Li, Te-Mao; Chiou, Jian-Shiun; Tsai, Fuu-Jen; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Chou, Chen-Hsing; Liang, Wen-Miin; Lin, Ying-Ju (Frontiers in Pharmacology, 2021)
Aplastic Anemia (AA) is a rare but fatal hematologic disease that may occur at any age and especially higher in Asia. We investigated whether Chinese herbal medicine (CHM) is beneficial to AA patients as a complementary therapy using a nationwide population-based database in Taiwan between 2000‒2016. Patient survival was estimated by Kaplan‒Meier survival analyses and Cox proportional-hazard model. CHM-users presented lower risks of overall and anemia-related mortalities when compared to non-users. The risk of overall mortality for CHM-users in AA patients was 0.70-fold (adjusted hazard ratio [aHR]: 0.70, 95% confidence interval [CI]: 0.66-0.74, p < 0.001). The risk of anemia-related mortality was lower in CHM-users when compared to non-users (aHR: 0.46, 95% CI: 0.32-0.67, p < 0.001). The association rule analysis revealed that CHM pairs were Ban-Zhi-Lian (BZL; Scutellaria barbata D.Don)→Bai-Hua-She-She-Cao (BHSSC; Oldenlandia diffusa (Willd.) Roxb.), followed by Dang-Gui (DG; Angelica sinensis (Oliv.) Diels)→Huang-Qi (HQi; Astragalus membranaceus (Fisch.) Bunge), and Xian-He-Cao (XHC; Agrimonia pilosa f. borealis (Kitag.) Chu)→Gui-Pi-Tang (GPT). Network analysis showed that BZL, BHSSC, DG, HQi, XHC, GPT, and Dan-Shen (DanS; Salvia miltiorrhiza var. charbonnelii (H.Lév.) C.Y.Wu) were commonly used CHMs for AA patients. Therefore, further studies for these commonly prescribed herbs are needed in functional investigations in hematopoiesis-stimulating effect and large-scale randomized controlled trials (RCT) in bone marrow failure related diseases.